The dependence of the fluorescent parameters of the Caspiy microseaweed from the anthropogenous pollution - M. Yu. Aliyeva; A. T. Mammayev; M. H.-M. Magomedova (Юг России: экология, развитие)
Anthropogenic pollution becomes the essential factor, reducing photosynthetic efficiency of microalgae of Caspian sea. Methods of registration of chlorophyll fluorescence can be used for detection of toxic action of heavy metals on microalgae.